Synergies in mergers and acquisitions in the copper mining industry - Matuszewski, Maciej (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The results of the research shall broaden the knowledge required for interpretation of synergy effects in the mineral mining sectors. The results obtained shall be used for further research when developing procedures for analysis and evaluation of the effects of mergers and acquisitions in the copper ore mining sector and may also be used by the management of an acquiring party involved in mergers and acquisitions in the copper mining sector. Aim: The aim of the research, the results of which has been presented in this article, was to identify areas of processes concerning operations and costs as possible sources of synergies in the merger and acquisition processes in the copper ore mining sector. A critical review of literature about the subject as well as desk research have been used to make the study. Results: The obtained results confirm the need for synergy effects, in the areas of both operations and costs, to be considered in the processes of mergers and acquisitions in the copper ore mining sector. Taking into account the strategy map and the cost structure in the copper mining sector, we may conclude that the costs of mining and milling are the key parameters of the cost structure (in relation to overheads) and they should be considered as the specific subject of due diligence, because apparently, this is the area where the greatest synergy value may be achieved.